Intravoxel incoherent motion diffusion‐weighted imaging of hepatocellular carcinoma: Is there a correlation with flow and perfusion metrics obtained with dynamic contrast‐enhanced MRI?. Issue 4 (26th February 2016) - Hectors, Stefanie J.; Wagner, Mathilde; Besa, Cecilia; Bane, Octavia; Dyvorne, Hadrien A.; Fiel, M. Isabel; Zhu, Hongfa; Donovan, Michael; Taouli, Bachir
Abstract : Purpose: To assess the correlation between intravoxel incoherent motion diffusion‐weighted imaging (IVIM‐DWI) and dynamic contrast‐enhanced magnetic resonance imaging (DCE‐MRI) metrics in hepatocellular carcinoma (HCC) and liver parenchyma. Materials and Methods: Twenty‐five patients with HCC (M/F 23/2, mean age 58 years) underwent abdominal MRI at 1.5 or 3.0T, including IVIM‐DWI (with 16 b‐values) and DCE‐MRI (3D FLASH sequence, mean temporal resolution of 2.3 sec). IVIM‐DWI parameters (pseudodiffusion coefficient, D*, diffusion coefficient, D, and perfusion fraction, PF) were quantified in HCC lesions and liver parenchyma using a Bayesian fitting algorithm. DCE‐MRI parameters (arterial flow, Fa, portal flow, Fp, total flow, Ft, mean transit time, MTT, distribution volume, DV, and arterial fraction, ART) were quantified using a dual‐input single‐compartment model. Correlations between IVIM‐DWI and DCE‐MRI parameters were assessed using a Spearman correlation test. Results: Thirty‐three HCC lesions (average size 5.0 ± 3.6 cm) were analyzed. D, D*, and PF were all significantly lower in HCC vs. liver ( P < 0.05). Significantly higher Fa and ART and lower Fp were observed in HCC vs. liver ( P < 0.001). Significant moderate to strong negative correlations were observed between ART and D* ( r = −0.443, P = 0.028), ART and PF ( r = −0.536, P = 0.006), ART and PFxD* ( r = −0.655, P < 0.001), Fa and PF ( r = 0.455, P = 0.023), and Fa and PFxD* ( r = −0.475, P = 0.018) in liver parenchyma. There was no significant correlation between IVIM‐DWI and DCE‐MRI metrics in HCC lesions. Conclusion: IVIM‐DWI and DCE‐MRI provide nonredundant information in HCC, while they correlate in liver parenchyma. These findings may be secondary to predominant portal inflow in the liver and tortuous vasculature and tissue heterogeneity in tumors. J. MAGN. RESON. IMAGING 2016;44:856–864.